Proton magnetic resonance spectroscopy-based evaluation of metabolic abnormalities in the right dorsolateral prefrontal cortex and caudate nucleus in treatment-naïve patients with obsessive-compulsive disorder - Gagan Hans; Uma Sharma; Novy Gupte; Ragul Ganesh; Vaibhav Patil; Pratap Sharan (Indian Journal of Psychiatry)
Background: Obsessive-compulsive disorder (OCD) is a common psychiatric disorder whose underlying pathophysiology is insufficiently understood. The pathophysiology of OCD may be related to abnormalities in the biochemistry of neurotransmitters. Aim: The aim of the present study was to measure the absolute concentration of various metabolites in the right dorsolateral prefrontal cortex (DLPFC) and caudate nucleus (CN) in treatment-naive patients with OCD and compare it with healthy controls (HCs). Methods: The present study investigated the metabolic profile of two brain regions, namely right DLPFC and CN, by using single voxel in-vivo proton magnetic resonance spectroscopy (1H MRS) in drug-naive patients with OCD (n = 17, mean age = 30.71 ± 10.104 years) and compared it with healthy controls (n = 13, mean age = 30.77 ± 5.449 years). The patients with OCD were recruited after appropriate psychometric assessments. The 1H-MRS experiments were performed using the 3 Tesla (3T) human MR scanner, and absolute concentrations of metabolites were estimated using the LC model. Results: Significantly lower concentration of tNAA in the right DLPFC was observed in the patients with OCD compared to the controls, which may be indicative of neurodegeneration in this region. However, no significant differences were observed in the concentrations of the metabolites between the patients and controls in the CN region. The level of tNAA in DLPFC significantly correlated with the disability level (WHO-DAS) of the patients. Conclusions: The present study demonstrates abnormalities in the metabolic profile of an important region, DLPFC of the CSTC circuit, which is suggestive of neurodegeneration in the region in OCD patients.